(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2023)
Problem solving ability is one aspect of higher order thinking skills. This study aims to determine the profile of students’ problem solving abilities in integrated environmental education on global warming material. This research is a quantitative descriptive study to obtain the required data and to analyze the level of problem solving abilities of students. The research subjects were 34 students of class XI MIPA SMAN in Jombang. The test instrument used in the form of 12 questions type description which refers to the indicator of problem solving ability used by Lestari. The results showed that the problem solving ability of students on global warming material was included in the medium category. Efforts to improve problem solving skills can be done through integrated physics learning in environmental education.